L∞-variational problems associated to measurable Finsler structures. (February 2016) - Guo, Chang-Yu; Xiang, Chang-lin; Yang, Dachun
Abstract: We study L ∞ -variational problems associated to measurable Finsler structures in Euclidean spaces. We obtain existence and uniqueness results for the absolute minimizers.